Series-Interconnected Plastic Dye-Sensitized Solar Cells Prepared by Low- Temperature Binder-Free Titania Paste - Rosa, Erlyta Septa; Muliani, Lia; Shobih, Shobih; Hidayat, Jojo; Yuliarto, Brian (Makara Journal of Technology, 2014)
The aim of this research is to study dye-sensitized solar cells (DSSC). This was implemented on a flexible polyethylene terephthalate (PET) substrate using a mixture of transparent and scattered mesoporous anatase-titania as the electron transport layer for the photoelectrode. This mixture of anatase titania performed a dual function of light scattering and efficient dye absorption. In this study, a porous nano-TiO2 film was prepared on indium tin oxide (ITO) coated polyethylene terephthalate (PET) by using a binder-free titania paste; on it, a DSSC was fabricated. The paste which contained a mixture of TiO2 nanoparticles, acid chloride, and ethanol was printed on two patterns of 1x6 cm2 active areas followed by sintered at 120 ºC to form TiO2 films. A commercial dye, N719, was adsorbed on the surface of TiO2 films and assembled to two platinized conductive plastic patterns to form a counter electrode and thus a sandwich-type dye cell. Finally, a solution of KI/I2 electrolytes was injected into the cell in which a couple of sandwich-type dye cells with an active area of 6 cm2 for each cell were series interconnected with a z-type interconnection between the photoelectrode of one cell and the counter electrode of another cell. The cell performance was characterized by employing simulated solar light at an intensity of 50 mW/cm2. The results showed interconnected cells generating a short-circuit photocurrent density of 2.34 mA/cm2, an open-circuit voltage of 1.10 volt, and overall 0.172% power conversion efficiency.